The association between sleep disturbances and tooth loss among post-stroke patients - VAGO, Eliana Lottenberg; FRANGE, Cristina; DA PAZ OLIVEIRA, Giuliano; JULIANO, Maria Ligia; MACHADO, Marco Antônio; COELHO, Fernando Morgadinho Santos (Arquivos de Neuro-Psiquiatria, 2022)
Background: Loss of teeth has been associated with neurological and sleep disorders. It is considered to be a predictor of stroke and leads to modifications of airway patency and predisposition to obstructive sleep apnea. Objective: To investigate sleep quality, risk of obstructive sleep apnea and excessive sleepiness among post-stroke patients with tooth loss attending the Neurovascular Clinic of the Federal University of São Paulo. Methods: The prevalence rates of different types of stroke were assessed among 130 patients with different degrees of tooth loss, along with the presence of sleep disturbances, risk of obstructive sleep apnea and excessive daytime sleepiness. Results: The prevalence of ischemic stroke was 94.6%, with either no significant disability or slight disability. Our sample had poor sleep quality, and a high risk of obstructive sleep apnea, but without excessive daytime sleepiness. Half of our sample had lost between 9 and 31 teeth, and more than 25% had edentulism. The majority used full removable dental prostheses, and more than half of these individuals slept without removing the prosthesis. Conclusions: We found high prevalence of poor sleep quality and high risk of obstructive sleep apnea among post-stroke patients with tooth loss. This indicates the need for further studies on treating and preventing sleep disturbances in stroke patients with tooth loss.
Keywords: Stroke; Sleep; Sleep Apnea, Obstructive; Jaw, Edentulous